Characteristics of the socio-geographical factors in the Drina-Velika Morava strategic direction zone - Inđić, Dejan Radivoj (Vojnotehnički glasnik / Military Technical Courier, 2013)
This paper presents the assessment of the operational – geographic features of the Drina–Velikamorava strategic direction. Due to the scope of the article, a variant of the assessment of the strategic direction is presented through its socio–geographic factors, while the mathematical–geographical and physical–geographic factors, as well as the operating lines of action are not discussed. Within the socio–geographic factors, the characteristics of the population, economy and communication networks are considered. The geographic area of the direction is nationally compact and provides war mobilization of units with no particular strain. The transportation network is not fully developed which makes combat operations difficult to attackers and facilitates them for the deffenders.. There are significant technical and technological potentials in the direction of the zone, but they are not evenly distributed. After the consideration of the complex socio – geographical factors, it is concluded that the shown strategic direction enables, without any special restrictions, a successful execution of combat operations in the long run. Introduction The Drina–Velikamorava strategic direction of action consists of two operational lines: Semberija–Šumadija and Glasinac–Zapadnamorava. This paper presents a variant of a complex evaluation of the socio–geographic factors in the area of strategic direction. Within the socio–geographic factors in the strategic direction, the characteristics of the population, economy and communication networks are discussed. Characteristics of the population and settlements In the geographic strategic direction, there is about 30% of the population of the Republic of Serbia. The highest population density is in major cities (Belgrade, Novi Sad, Šabac, Čačak, etc.). The space is nationally compact, and over 95% of the population are Serbs. In terms of building methods,there are the following types of settlements: compact type (including cities and villages in the plains of Mačva, Posavina, Morava) scattered type (including villages in the mountainous regions – Tara, Zlatibor and Maljen, Povlen) and mixed type (spa, mining and tourist resorts). It should be noticed that almost all the towns on the line are located along the most important communication lines, in major river valleys, at mountain foothills, namely in the geographic space naturally suitable for combat operations. Characteristics of Communication Networks The communications network on the strategic direction is not developed well and does not provide for a high tempo of well–equipped agressor attacks. Through this strategic geographic space there are two longitudinal directions (Bačka–Kosovo and Bačka–Crnagora) and two transverse (Šumadija– Timok and Zapadnamorava–Nišava) communication nodes.. The communication networks in the geographic direction enable successful maneuvers and regrouping of forces in the front and rear, successful execution of combat operations, timely and successful execution of mobilization and evacuation. In the geographic strategic direction, the river and canal traffic does not follow the natural and geographic conditions, so it is of no special significance to the military aspect. The general characteristics of air traffic in the strategic direction is an unfavourable territorial distribution of airports (in the southeast direction). Characteristics of the economy The consideration of the economy in this strategic direction is done through the consideration of the military geographic characteristics of natural–economic potential and military geographic characteristics of technical–economic and technological potentials. The natural economic resources are viewed through: agricultural land, energy resources and mining potential. Much of the farmland is located in the Semberija–Šumadija operating direction (Mačva, Pocerina, Šumadija) that gravitates towards the periphery. In the strategic direction, the major geographic sources of energy are waterpower and coal while oil and gas are not sufficiently represented. The diversity of non–metal ores and metals is of invaluable importance because they form the basis for the production of a variety of funds for strengthening the defense capability of the country. Technical and Economic Technological resources are exposed through the major characteristics of agriculture and industry in the area of strategic direction. Within the geographic strategic direction, there are two agricultural areas: the Pannonian agricultural area (south of the Sava and the Danube rivers), with wheat and corn as strategic raw materials and the mountainous agricultural area (including the border area of ​​the Pannonian agricultural field to the right border of the strategic direction) with many cultures (especially plums, apples, pears, cherries, apricots, walnuts, etc.). There are two industrial areas set aside the strategic direction: Pannonia–Belgrade (Belgrade allocated industrial area) and the central industrial area (there are two industrial areas: Timok–Morava and Zapadna Morava). Industrial production in the strategic direction is well developed, especially in energy, mining and metal industries. Conclusion Based on the complex understanding of the socio – geographic factors in the Drina–Velikamorava strategic direction, it can be concluded that the strategic direction shown enables successful combat operations over an extended period of time. Some problems may occur due to unevenly distributed technical and technological potentials and a potential use of weapons of mass destruction in the vicinity of large cities in the area of strategic direction.